Policy roadmap for a sustainable informal business sector. Issue 8 (17th November 2022) - Modiba, Florah S.; Mago, Stephen
ABSTRACT : The informal sector plays a vital role in providing income opportunities to the unemployed. The sector can create more employment opportunities in this distressed South African economy; however, sustainability concerns do exist. An exploratory research design was used in this qualitative study in order to understand the policy stances towards the informal business sector and the issues that threaten its sustainability. The results indicated that the government's efforts to support informal businesses are not tangible and are not focused on inclusive development. A strategic roadmap that could be used by the government to help the sector sustain itself is proposed.